Character Education in English Language Teaching (ELT): A Literature Review Article - Ilham Agung Prasetyo; Didi Suherdi; Ahmad Bukhori Muslim (Cakrawala Repositori IMWI, 2023)
Character education is important since students should not only be smart but also have good character. Character education is the deliberate effort by all stakeholders to instil good character values in students therefore it should be integrated into all subjects taught. This research purpose is to evaluate and summarize current research on the incorporation of character education in English Language Teaching (ELT) in a systematic manner. This research is a literature review research. The method used is a literature review of articles from previous studies, which are related to the integration of character education in English Language Teaching (ELT). An electronic search was conducted to identify 25 relevant studies from several databases. The results of 25 studies show that English Language Teaching (ELT) is an excellent medium for cultivating character education in students, especially through literary texts. This research also provides insight for future research and gives specific recommendations for further study related to the integration of character education in online learning.